A Systematic Study on the Effects of Process Parameters on Spinning of Thin-Walled Curved Surface Parts With 2195 Al-Li Alloy Tailor Welded Blanks Produced by FSW - Zhang, Hongrui; Zhan, Mei; Zheng, Zebang; Li, Rui; Lyu, Wei; Lei, Yudong (Frontiers in Materials, 2021)
The manufacturing process is inevitably accompanied with the occurrence of scraps, which leads to resource waste and environmental pollution. Recycling and remanufacturing are the most used approach for metal scraps from the perspective of the well-established advantages from the economic and environment. In this study, spinning experiments with 2195 Al-Li alloy tailor welded blanks produced by welding from metal scraps were conducted under different process parameter designs. And then the effects of various process parameters on spinning of thin-walled curved surface parts were systematically studied. The results of the corresponding experimental groups show that the roller attack angle, the spinning clearance and the installation method of tailor welded blanks have the most significant effect on the weld torsion angle. In addition, it was found that along the longitude direction of spun parts, the surface roughnesses of the weld of spun parts have been greatly improved under the roller nose radius of 10 mm, the spinning clearance of 1.0 mm, the constant linear velocity and the installation method of tailor welded blanks of the LSSBSR, respectively, while the process parameters have little significant effect on the surface roughness along the latitude direction of spun parts. Furthermore, it can be concluded that the forming profiles of spun parts fitted the mandrel well under the roller nose radius of 6 mm, double rollers, the roller attack angle of 30° and 45°, spinning clearance of 1.5 mm and the installation method of tailor welded blanks of the USSBSR, respectively. The research results will provide guidance for the precise spinning forming of thin-walled curved surface parts with tailor welded blanks. Thereby, it is also beneficial for green manufacturing involving in recycling and remanufacturing of metal scraps.